Association Study of ERβ, AR, and CYP19A1 Genes and MtF Transsexualism. (1st December 2014) - Fernández, Rosa; Esteva, Isabel; Gómez-Gil, Esther; Rumbo, Teresa; Almaraz, Mari Cruz; Roda, Ester; Haro-Mora, Juan-Jesús; Guillamón, Antonio; Pásaro, Eduardo
Abstract: Introduction: The etiology of male-to-female (MtF) transsexualism is unknown. Both genetic and neurological factors may play an important role. Aim: To investigate the possible influence of the genetic factor on the etiology of MtF transsexualism. Methods: We carried out a cytogenetic and molecular analysis in 442 MtFs and 473 healthy, age- and geographical origin-matched XY control males. The karyotype was investigated by G-banding and by high-density array in the transsexual group. The molecular analysis involved three tandem variable regions of genes estrogen receptor β ( ER β) (CA tandem repeats in intron 5), androgen receptor ( AR ) (CAG tandem repeats in exon 1), and CYP19A 1 (TTTA tandem repeats in intron 4). The allele and genotype frequencies, after division into short and long alleles, were obtained. Main Outcome Measures: We investigated the association between genotype and transsexualism by performing a molecular analysis of three variable regions of genes ERβ, AR, and CYP19A 1 in 915 individuals (442 MtFs and 473 control males). Results: Most MtFs showed an unremarkable 46, XY karyotype (97.96%). No specific chromosome aberration was associated with MtF transsexualism, and prevalence of aneuploidy (2.04%) was slightly higher than in the general population. Molecular analyses showed no significant difference in allelic or genotypic distribution of the genes examined between MtFs and controls. Moreover, molecular findings presented no evidence of an association between the sex hormone-related genes ( ER β, AR, and CYP19A 1 ) and MtF transsexualism. Conclusions: The study suggests that the analysis of karyotype provides limited information in these subjects. Variable regions analyzed from ER β, AR, and CYP19A 1 are not associated with MtF transsexualism. Nevertheless, this does not exclude other polymorphic regions not analyzed.